User perspectives and preferences on a novel TB LAM diagnostic (Fujifilm SILVAMP TB LAM): a qualitative study in Malawi and Zambia - Herrmann, Yannis; Lainati, Federica; Castro, María del Mar; Mwamba, Chanda P.; Kumwenda, Moses; Muyoyeta, Monde; Broger, Tobias; Heinrich, Norbert; Olbrich, Laura; Corbett, Elizabeth L.; McMahon-Rössle, Shannon A.; Engel, Nora; et al. (PLoS global public health, 2022)
Widely available tuberculosis (TB) diagnostics use sputum samples. However, many patients, particularly children and patients living with HIV (PLHIV), struggle to provide sputum. Urine diagnostics are a promising approach to circumvent this challenge while delivering reliable and timely diagnosis. This qualitative study in two high TB/HIV burden countries assesses values and preferences of end-users, along with potential barriers for the implementation of the novel Fujifilm SILVAMP TB-LAM (FujiLAM, Fujifilm, Japan) urine test. Between September 2020 and March 2021, we conducted 42 semi-structured interviews with patients, health care providers (HCPs) and decision makers (DMs) (e.g., in national TB programs) in Malawi and Zambia. Interviews were transcribed verbatim and analyzed using a framework approach supported by NVIVO. Findings aligned with the pre-existing Health Equity Implementation Framework, which guided the presentation of results. The ease and convenience of urine-based testing was described as empowering among patients and HCPs who lamented the difficulty of sputum collection, however HCPs expressed concerns that a shift in agency to the patient may affect clinic workflows (e.g., due to less control over collection). Implementation facilitators, such as shorter turnaround times, were welcomed by operators and patients alike. The decentralization of diagnostics was considered possible with FujiLAM by HCPs and DMs due to low infrastructure requirements. Finally, our findings support efforts for eliminating the CD4 count as an eligibility criterion for LAM testing, to facilitate implementation and benefit a wider range of patients. Our study identified barriers and facilitators relevant to scale-up of urine LAM tests in Malawi and Zambia. FujiLAM could positively impact health equity, as it would particularly benefit patient groups currently underserved by existing TB diagnostics. Participants view the approach as a viable, acceptable, and likely sustainable option in low- and middle-income countries, though adaptations may be required to current health care processes for deployment. Trial registration: German Clinical Trials Register, DRKS00021003. URL: https://www.drks.de/drks_web/setLocale_EN.do